ACCOUNTING FOR BUSINESS ETHICS AND SUSTAINABILITY (A4BES): HARMONIZING ACCOUNTING FOR THE INTERESTS OF SHAREHOLDERS AND NON-SHAREHOLDER STAKEHOLDERS - Setiono, Bambang (Indonesian Journal of Accounting and Governance, 2024)
The purpose of this study is to introduce a framework that assists corporate managers in transforming the promised benefits of sustainability reports into future financial performance by aligning the interests of shareholders and non-shareholder stakeholders. This descriptive study proposes a framework to investigate the stakeholder harmonization process undertaken by managers, with a pilot study focusing on Indonesian mining companies using content analysis methodology. The study hypothesizes that managers' disclosures in sustainability reports reflect their success in achieving stakeholder harmony. Modern corporate managers accomplish stakeholder harmonization by reporting on both financial performances and non-financial performances, I called them Business Ethics and Sustainability (ABES) performances. They provide outcome-based performance information on A4BES performances. The study found that Indonesian mining companies typically disclose more information than required by the capital market regulation on sustainability reporting. Mining managers, categorized as conventional managers at the second level of the stakeholder harmonization process, report over 50% of A4BES accounts but often omit outcome-based performance information. This study extends sustainability accounting literature on stakeholder theory by examining how management processes balance the interests of shareholders and non-shareholder stakeholders.